Structural, dielectric, and impedance study on ZnO doped Sr(Fe 0.5 Nb 0.5 )O 3 ceramics - Thanatep Phatungthane (2019)
© 2018 Elsevier B.V. SrFe 0.5 Nb 0.5 O 3 (SFN) ceramics doped with ZnO were synthesized via a conventional mixed oxide technique. Phase formation investigation by X-ray diffraction technique (XRD) revealed that all ceramic samples exhibited pure perovskite phase. Grain size as observed by an electron microscopy (SEM), was found to decrease with increasing the additive concentration. Dielectric properties and other related properties of the ceramics were also investigated. Very high dielectric constants >3.3 × 10 5 (at temperature 250 °C and 1 kHz) were found for the 3 vol% doped samples. The impedance spectroscopy analysis suggested that the dielectric behavior of the samples could be linked with the Maxwell - Wagner polarization mechanism.